If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-1(2x-3)=1
We move all terms to the left:
8x-1(2x-3)-(1)=0
We move all terms containing x to the left, all other terms to the right
8x-1(2x-3)=1
| 5x-8+4x+1=180 | | =7p+p+4p+2p-6 | | 5x+10=2x-50 | | 26=7x-3x-6 | | -2(x+3)-2x=-2x+10 | | 16x-8=9x+6 | | 0=-4.9x^2+10 | | 6y=81 | | 2(m+7)=7m-16 | | -37=7a-9 | | |c–2|=2c-10 | | 8x-7=7x+52 | | 2m-15+6m=65 | | 2(d-38)=52 | | 2y+8=8+2y | | -3(2x-4)+10=3x-5 | | f=-3^2-27-7 | | 4(4x-5)=108 | | 5x+21=81 | | 1+8x=7583 | | 1+7b=-5+8b | | 20+x+8=3x-11 | | -3t-10=-3t | | 5(x=5+2(x-1) | | 40+-2f=98 | | 0=-4.9x^2-10 | | 5x-37=-100-2x | | -5(x-9)=30-2 | | 11x-42=2x-51 | | 4(x+20)=2x+1 | | 6(-6x-8)=-84 | | 5x=10-5 |